Implementasi Strategi Penyelesaian Pembiayaan Produk Murabahah Bermasalah (Studi pada BMT Muamalah Tulungagung) - Tri Hardono Purbo Kusumo; Mei Santi (Transformasi : Jurnal Studi Agama Islam, 2021)
Murabahah product financing at BMT Muamalah Tulungagung is the product most interested in by members, but in its implementation there are often problems such as non-progress of installments, doubt and traffic jams. If these problems are not minimized and resolved with an effective strategy, it will certainly affect the sustainability of the BMT business. The formulation of the problem is as follows: What is the strategy in dealing with problematic murabahah product financing at BMT Muamalah Tulungagung? and What are the factors that accelerate the resolution of murabahah product financing problems at BMT Muamalah Tulungagung ?. The research method is included in field research and in the type of qualitative descriptive research. Based on the research results, it can be argued that the strategy in overcoming problematic murabahah product financing at BMT Muamalah Tulungagung has been implemented based on the provisions of the DSN-MUI fatwa. The strategy applied is adjusted to the criteria for the problem and the character of the members which include: first, for problems when the installment failure is resolved through a persuasive approach, if it is not deliberate and members still have good faith, BMT will be given relief. Second, for members whose financing quality is doubtful, it will be resolved through a correspondence administration strategy, starting from invitation letters, warning letters (SP-1, SP-II and SP-III). Third, the final strategy if there is non-performing financing and members are negligent or do not have good faith, it will be resolved through sales or collateral execution. As for the factors that accelerate the resolution of murabahah product financing problems at BMT Muamalah Tulungagung, among others, the BMT is making serious efforts towards the resolution and from its members also have the responsibility, are willing to be cooperative and have good faith to immediately resolve the problem by means of which has been determined by BMT Muamalah Tulungagung.